A "Pedagogia" da Feira Livre de São Bento: narrativas, saberes e práticas educativas na cidade de Cascavel - CE - Silva, Francisca Eliana Santos da (2014)
In this study , we sought to understand the educational practices and knowledge present in the fair of St. Benedict , in the city of Cascavel - EC which is distant 64 km from Fortaleza . For this survey , we chose as Brandão (2005 ) theoretical support ; Durkheim (2007 ) ; Burke ( 2003); Huberman (1976) and Certeau (1998). We chose the qualitative approach and used the literature to support the clarification of the subject investigated . We also use the case study that provided the most information gathering and deepening of the educational practices of the merchants . During data collection, the methodological approach chosen was participant observation with the support of a field journal, and semistructured interviews with the protagonists of the research. We seek to pursue a path in oral history to understand the relationship of stallholders with the fair, and we realize that the work at the fair receives affective characteristics that strengthens ties between marketer and fair. We saw that the show is more of an environment for buying and selling products , we observe that this space born life histories , knowledge that grow from experiences in everyday practices . We also point out that informal environments also manifest educational practices and this shows that education is a free phenomenon. Therefore, the street fair of St. Benedict is a social, cultural and educational event that contributes to the survival of many families.